Lean Manufacturing Assessment to Reduce Waste in Calendar Manufacturing Using Kanban System - Athallah, Panji; Pradana, Bayu Ilham (Jurnal Management Risiko dan Keuangan, 2025)
Purpose –  This study aims to evaluate the production process at PT Libies Media Grafika and provide recommendations for improvement through the implementation of lean manufacturing and the Kanban system.   Design/methodology/approach – This applied research employs a quantitative descriptive approach. Data were collected through interviews, document reviews, and direct observations of the company's production process. Lean manufacturing principles and the Kanban system were applied to identify and reduce waste while improving process efficiency.   Findings – The study identifies several sources of waste, including delays in material handling during molding, unnecessary material transportation during quality control, and product defects such as paint flaking and glue separation. The implementation of the Kanban system reduces waste and improves the Value-Added (VA) ratio from 53.47% to 55.19%, resulting in a more organized and efficient production process.   Originality/value – This study demonstrates the practical integration of lean manufacturing and the Kanban system to improve production efficiency in the printing industry, providing empirical evidence of waste reduction and value-added enhancement through workflow optimization.